Social and Political Views of Jokūbas Jasinskis - Vansevičius, Stasys (Problemos, 1972)
Jokūbas Jasinskis was the organiser and leader of the 1794 uprising in Lithuania. He held radical views, adhered to the Jacobinic system of terror against traitors and proclaimed the struggle for universal equality. He called to forget class distinctions and defend the native land. This, however, proved to be not sufficient for mass participation of peasants in the uprising. J. Jasinskis was a supporter of the republican and sovereign Lithuania, independent of Poland. Because of his radical views he fell into disgrace of the Polish gentry and was dismissed from the post of the commander of the Lithuanian Army. J. Jasinskis was killed on the 4th of November, 1794, in the defence of Warsaw.